To find the equation of the exponential function, we can use the general form of an exponential function: y = ab^x, where y is the dependent variable, x is the independent variable, a is the initial value, and b is the base.
Let's substitute the values from the table into the general form of the equation to find the values of a and b.
For x = 0, y = 5:
5 = ab^0
5 = a
For x = 1, y = 2.5:
2.5 = 5b
b = 2.5/5
b = 0.5
Therefore, the exponential function represented by the table is:
y = 5 * (0.5)^x
Find the equation of the exponential function represented by the table below:
x y
0 5
1 2.5
2 1.25
3 0.625
1 answer